Steric Properties of N‐Heterocyclic Carbenes affect the Performance of Electronic Probes. Issue 47 (30th November 2021) - Barnett, Christopher; Cole, Marcus L.; Harper, Jason B.
Abstract: Electronic probes of ligands, particularly carbenes, are widely used in assessing electronic properties; the results inform the selection of a ligand for a given application. As such, it is important to ensure the data obtained is reliable and unaffected by other factors, such as the steric bulk of the ligand. The effects of such steric factors on two commonly used electronic probes (based on palladium and selenium) are investigated here, with the selenium adduct found to be particularly sensitive. It is hoped that this serves as a cautionary tale to always critically evaluate what a probe is measuring. Abstract : Size matters . The impact of the size of the N ‐substituents of N ‐heterocyclic carbenes on two common NMR based electronic probes has been investigated, highlighting that care must be taken to ensure the probe gives meaningful information of the ligand properties. That is, make sure you measure what you want.